2021
DOI: 10.21037/atm-21-2346
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PYCARD is an independent predictor of unfavorable prognosis and chemotherapy resistance in glioma

Abstract: Background: PYD and CARD domain-containing (PYCARD) was upregulated in TMZ-resistant cell lines and glioma tissue and was correlated with poor prognosis, its role in glioma is unclear known. The aim of this study was to elucidate the relationship between PYCARD and glioma based on Gene Expression Omnibus (GEO), The Cancer Genome Atlas (TCGA), and Chinese Glioma Genome Atlas (CGGA) databases.Methods: Glioma-resistant cells were compared with parental cells based on the GSE53014 and GSE113510 data sets. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…PYCARD, the adaptor protein of inflammasome, plays an important role in tumor carcinogenesis and progression, as confirmed by increasing evidence [ 14 , 54 ]. In our study, we found that PYCARD expression varied among human cancers and correlated to prognosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…PYCARD, the adaptor protein of inflammasome, plays an important role in tumor carcinogenesis and progression, as confirmed by increasing evidence [ 14 , 54 ]. In our study, we found that PYCARD expression varied among human cancers and correlated to prognosis.…”
Section: Discussionmentioning
confidence: 92%
“…It is interesting to note that PYCARD silencing did not influence apoptosis-related expression levels in cancer cell lines. In glioma, similarly, ectopic PYCARD expression increased the viability and migration abilities of tumor cells [ 54 ]. These studies appeared to be independent of the pro-apoptotic effects of PYCARD.…”
Section: Discussionmentioning
confidence: 99%
“…CASP9 is a protein-coding gene, and many reports have shown that CASP9 gene polymorphisms are associated with increased tumor risk, but this conclusion is controversial [31,32]. In gliomas, high expression of PYCARD is related to poor patient prognosis and is used as an independent predictor of chemoresistance [33]. However, the model shows high risk is positively associated with low overall survival as well as higher stage, and targeting these genes is a new option for therapy of ccRCC sick persons.…”
Section: Discussionmentioning
confidence: 99%
“…PRKACA is one of the catalytic subunits of protein kinase A, and was found to mediate resistance to HER2-targeted therapy in breast cancer [49]. PYCARD is an adaptor protein that assembles the in ammasome, high expression of which was considered to be an independent predictor of unfavorable prognosis in glioma and could promote glioma cell proliferation and migration [50]. SCAF11, also known as caspase-11, is a pro-in ammatory enzyme, which may have a role in cancer-associated angiogenesis [51].…”
Section: Discussionmentioning
confidence: 99%